Mol-Eye: A New Metric for the Performance Evaluation of a Molecular Signal - Turan, Meric; Kuran, Mehmet Sukru; Yilmaz, H. Birkan; Chae, Chan-Byoung; Tugcu, Tuna (IEEE, 2018)
Inspired by the eye diagram in classical radio frequency (RF) based communications, the MOL-Eye diagram is proposed for the performance evaluation of a molecular signal within the context of molecular communication. Utilizing various features of this diagram, three new metrics for the performance evaluation of a molecular signal, namely the maximum eye height, standard deviation of received molecules, and counting SNR (CSNR) are introduced. The applicability of these performance metrics in this domain is verified by comparing the performance of binary concentration shift keying (BCSK) and BCSK with consecutive power adjustment (BCSK-CPA) modulation techniques in a vessel-like environment with laminar flow. The results show that, in addition to classical performance metrics such as bit-error rate and channel capacity, these performance metrics can also be used to show the advantage of an efficient modulation technique over a simpler one.
Yilmaz, H. Birkan/0000-0002-4773-2028;
Keywords: Molecular Communication; Nanonetworks; Communication via Diffusion; Vessel-Like Environments; Eye Diagram